(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article investigates the role of songs and pictures in enhancing the learning experience of school children, particularly at the primary education level. With the growing emphasis on interactive and student-centered teaching methods, educators are increasingly turning to creative tools to make lessons more effective. Songs, with their rhythm and repetition, help students memorize new information, improve language and listening skills, and create a joyful classroom atmosphere. Meanwhile, pictures support visual learning by making abstract ideas more concrete, developing critical thinking, and aiding comprehension. The article discusses theoretical foundations, psychological benefits, and practical classroom applications of using songs and images in various subjects such as language arts, science, and social studies. Based on classroom observations and educator feedback, the article concludes that combining auditory and visual elements fosters better student engagement, long-term retention, and a deeper emotional connection to the material.